Screening for lower genital tract infections in women of reproductive age group attending a tertiary care hospital - Murugesan, Malathi; Arumugam, Vijayalakshmi; Gomatheeswari, Nithya; AV, Sowmya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Lower genital tract infections are the major cause of gynecological morbidity and a great public health concern in India. Inadequate laboratory diagnostic facilities in all the levels of health care, limited resources in material and manpower, stigma and discrimination associated with RTI services are some of the reasons of lack of exact incidence/prevalence rate of RTI in India. Hence this study was conducted to provide a reliable laboratory based data on the occurrence of lower genital tract infections. Methods: A prospective study was conducted on 110 women attending Gynecology OPD at a tertiary care teaching hospital over a period of one year (June 2014 to May 2015). After getting informed consent and brief history, vaginal swab and endocervical sample was collected and used for microscopic examination and culture. All the endocervical samples were subjected to Real Time PCR for detection of Chlamydia trachomatis. Results: Among 110 samples, laboratory diagnosis of lower genital tract infections was positive in 43 subjects (39.09%). By Real time PCR assay among the 110 samples, 9 (8.8%) of the samples were positive for Chlamydia trachomatis infection. Candida sp., (17, 35.42%) was the most common organism identified followed by Escherichia coli (10, 20.83%). Conclusions: Laboratory screening is must in all the symptomatic women in order to avoid the unnecessary treatment, which warrants the patients’ reliability. Chlamydia trachomatis screening is mandatory for all the child bearing age group women to avoid consequences like PID and infertility.